Hubungan Perilaku Bullying Terhadap Konsep Diri Remaja di Kelurahan Pilangbango Kota Madiun - Felix Trisuko Nugroho (JKI (Jurnal Konseling Indonesia), 2022)
This research was conducted to determine the relationship between parents' bullying behavior and adolescent self-concept in Kelurahan Pilangbango. This type of research is quantitative with a correlational approach, namely to see a relationship. The population in this study were teenagers who were in Kelurahan Pilangbango with a total sample of 60 people. The research data was obtained using a Likert scale model questionnaire, then distributing the questionnaire via the Google form. The analytical method uses the product moment test with a correlation result of -0.205 (-2.05%) and a significant value level of 0.115 (P > 0.05) in the category of weak relationship with a negative direction. As for the R Square test, the determination value is 4.2% and the remaining 95.8% is influenced by other variables not examined in this study, such as peer factors, the surrounding environment, social media and learning outcomes. It can be concluded statistically that there is a significant relationship between parents' bullying behavior on adolescent self-concept which is negative. The higher the parents' bullying behavior, the lower the adolescent's self-concept. Thus, Ha who stated that there was a significant relationship between Parental Bullying Behavior and Adolescent Self-Concept in Kelurahan Pilangbango was accepted and Ho who stated that there was no relationship between Parental Bullying Behavior and Adolescent Self-Concept in Kelurahan Pilangbango was rejected.